The potential use of leech, dhab lizard and mudskippers for men's sexual health: a scoping review / Idham Fitriadi Erwandy ... [et al.] - Erwandy, Idham Fitriadi; Hamdani, A Hasan; Abdul Rashid, Muhammad Farhan; Mohd Shahrol, Nur Izzati; Hatah, Ernieda (Faculty of Medicine, 2024)
Introduction: The use of animals for medical treatment or zootherapy has been reported all over the world. This study aims to assess the potential use of leech, dhab lizard and mudskipper for men’s sexual health, particularly in the treatment of erectile dysfunction (ED). Methods: Using systematic review study design, relevant articles were located from three electronic databases, which are OvidMEDLINE, Google Scholar and PubMed. A total of 180 articles were searched from the electronic databases and 10 journal articles were included in the study. Another 12 articles were identified from hand-search of reference list. Results: There were limited human studies reporting the use of the leech, mudskipper and dhab lizard for men’s sexual health. Hence, the efficacy and safety of the aforementioned zootherapy were not able to be determined. Conclusion: A recommendation for well-designed studies in vitro and in vivo are needed before the animal’s product and derivatives can be used in clinical trials.